IMPLEMENTASI MANAJEMEN MUTU DALAM MENINGKATKAN SARANA DAN PRASARANA SEKOLAH: Studi Kasus di SMK As- Syafa'ah Sumbersari Jember - BADRUT TAMAMI (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2021)
The increasing number of educational institutions of various levels, starting from the levels of early childhood education, kindergarten, elementary, junior high and high school under the auspices of the Ministry of National Education or those at the RA, MI, Mts, and MA levels in the Ministry of Religion, indicates that the community is getting easier and easier access to education. affordable, it remains how the community can choose and sort out the quality provided by each educational institution, because there are differences in management and management that make an institution more advanced and stagnant. The purpose of quality management in schools is to provide convenience in accessing information both in service and relations between educational institutions, correspondence, and administrative and spatial arrangements that can make students more active and comfortable in the teaching and learning process at school. therefore it is necessary to have quality management and improvement of the quality of infrastructure in schools. The research method at this time the writer uses descriptive research type with a qualitative approach that will make it easier for the author to map, and formulate problems and their solutions.